ANALISIS PENATAAN KAWASAN SIMONGAN BERDASARKAN PERDA NO. 14 TAHUN 2011 TENTANG RENCANA TATA RUANG WILAYAH KOTA SEMARANG TAHUN 2011-2031 - Dini Noviani; Turtiantoro .; Rina Martini (Journal of Politic and Government Studies, 2015)
Industrial development is not simply about the significant contributions for national economic growth , but also provide more jobs for the unemployment rate in Indonesia. Especially in Semarang, industrial development in the Semarang City hit by the problems that Perda No. 14 Tahun 2011 about to the regional landscaping plan Semarang City 2011-2031 which in it is because the management of the area set Simongan a mixture of investments from the industry and settlement be residential compound.In this research, researchers used a method of qualitative data will produce a descriptive. To obtain the purpose of research data sources in accordance, researchers using a technique purpose of sampling to do an interview with The Planning and Regional Development of Semarang City, The Office of Town Planning and Housing the Semarang City, House of Representatives of Semarang City, The Industry Simongan Semarang, Workers and People who live in the area of Simongan Semarang.The research results show that the arrangement Simongan area must be done for a long time because the area was not a Simongan the Industrial Park, designation but the area of settlement goods and services trading. See the Simongan area along the Kaligarang’s river was also considered less ideal as an industrial park for because in worried about will have an impact on a river that pollution which a brook Kaligarang be used as a source of springs in the Semarang City.The scientists, in definition the spatial planning should be on all agreement includes minorities. So it makes the spatial planning is not only the relevant authorities. And the industry which stood at the Simongan must consider the rules and regulations.Keywords: Planning Area, Simongan Area, Regional Landscaping Plan